Identifying clinical features and molecular characteristics of the endometrial clear cell carcinoma - Cai, Yuhan; Han, Qin; Guo, Hongyan (Frontiers in Oncology, 2023)
Objective The aim of this study was to verify TCGA subtypes in endometrial clear cell carcinoma (ECCC) and determine their clinical and molecular characteristics. Methods We summarized and compared the clinical features of 28 clear cell carcinoma and 112 endometrioid carcinoma patients. Of the 28 ECCCs, 19 underwent TCGA classification, and other markers (ER, PR, ARID1A, ARIB1B, TAF1, and HER-2) were also detected by IHC, and outcomes were assessed. Results Compared to endometrioid carcinoma, ECCC had an older age of onset (median age, 64.5 years, range 31–81 years), higher rate of myometrial invasion (42.8% vs. 21.5% in endometrioid carcinoma), LVSI (33% vs. 16%), and more advanced FIGO stage. Among the ECCCs, LVSI was a poor prognostic factor. TCGA classification was performed for 19 ECCCs: two POLEmut cases (10.5%), three MMRd (15.8%), 11 p53wt (57.9%), and three p53abn (15.8%). Of the 19 ECCCs, six (31.6%) showed HER-2 positive expression, and eight (42.1%) had TAF1 expression loss. ECCCs possessed HER-2 and TAF1 expression had worse outcomes. Conclusion Our study summarized the clinical features of ECCC. The outcomes of patients with ECCC with TCGA subtypes differed from those of patients with endometrioid carcinoma. HER-2 and TAF1 may be new prognostic factors.